Integrating Social Enterprise for Cultural Landscape Conservation: A Case Study of Koh Plubpla, Ratchaburi Province, Thailand - Lertpaisarn, Tarmtor; Tovivich, Supitcha (Journal of Community Development Research (Humanities and Social Sciences), 2024)
This study focuses on exploring the dynamics of cultural change resulting from the transformation of agricultural land into commercial use through agritourism development. The concept of social enterprise is utilized as a core mechanism to manage community-centric landscape management and sustainably promote cultural landscape conservation. This qualitative research was conducted in Koh Plub Pla Subdistrict, Ratchaburi Province, with data collected from 60 primary informants and 12 key informants through in-depth interviews and focus group discussions. Additionally, three successful farm stay businesses in Ratchaburi Province were selected for interviews, based on criteria emphasizing compliance with agritourism quality standards established by the Department of Agricultural Extension.            The analysis applied the conceptual framework of “looking back to move forward”, integrating perspectives from contemporary vernacular architecture and sustainable development principles. The findings reveal that the social enterprise approach enhances integrated agriculture, generates economic benefits for local communities, and effectively conserves natural resources. However, project development in the study area faces complex challenges arising from local contexts. Adapting to socio-economic conditions and policy frameworks is essential for sustainable project planning. Strengthening collaboration among stakeholders, building community capacity, and addressing environmental factors are key to achieving smooth development aligned with both vertical and horizontal dimensions of the local context.            Furthermore, this study proposes a novel approach emphasizing the integration of social enterprise with cultural landscape management that prioritizes community participation. This integration aims to ensure appropriate land use and foster sustainable economic growth in the future.  Keywords:   Social Enterprise, Community-Centric Landscape Management, Sustainable Development, Cultural Landscape Conservation, Community Participation